Disodium-fosfomycin pharmacokinetics and bioavailability in post weaning piglets - Soraci, Alejandro Luis (2011)
Disodium-fosfomycin pharmacokinetics has been studied in different species after oral, intravenous, intramuscular and subcutaneous administration. At present there are neither documented clinical experiences of the use of fosfomycin in pigs nor any published studies in weaning piglets, although it is a period of high incidence of infectious diseases. The pharmacokinetics and the bioavailability of sodium fosfomycin were studied in post weaning piglets after intravenous and intramuscular administration of 15mg/kg of body weight. Plasma concentrations were measured by a high-performance liquid ms/ms. After IV administration the area under the fosfomycin concentration:time curve in plasma was AUC(0-12) of 120.00±23.12μgh/ml and the volume of distribution (Vd) of 273.00±40.70ml/kg. The elimination was rapid with a plasma clearance of 131.50±30.07ml/kg/h and a T1/2 of 1.54±0.40h. Peak serum concentration (Cmax), Tmax, AUC(0-12) and bioavailability for the IM administration were 43.00±4.10μg/ml, 0.75±0.00h, 99.00±0.70μgh/ml and 85.5±9.90% respectively. Different authors have determined a minimum inhibitory concentration (MIC90) ranging from 0.25μg/ml for Streptococcus sp. and 0.5μg/ml for Escherichia coli. Considering the above, and according to the values of plasma concentration vs time profiles observed in this study, effective plasma concentrations of fosfomycin for sensitive bacteria can be obtained following IV and IM administration of 15mg/kg in piglets.